Determinants of Pneumonia in Toddlers in Jambi City - M. Dody Izhar (Jurnal Berkala Epidemiologi, 2021)
Background: Pneumonia is an acute respiratory infection and the second leading cause of toddler deaths in Indonesia. Nutritional status, immunization status, and humidity in the house constitute risk factors for the incidence and prevalence of pneumonia. Purpose: The objective of this research is to analyze the determinants of nutritional status, immunization status, and air humidity against the incidence of pneumonia in toddlers in Jambi City. Methods: This was an observational study. A case-control design approach was adopted. The research location was the Public Health Center of Talang Bakung in Jambi City, which has the highest prevalence of pneumonia cases. This study was conducted from January 2019 to August 2019. The number of samples in this study was 66 toddlers, with a 1:1 ratio of cases. Data was collected using a multistage random sampling technique. Primary and secondary data obtained was analyzed with a logistic regression test method. Results: The highest proportion of pneumonia cases was observed in toddlers between the ages of 12 and 35 months (75.76%). The proportion of female toddlers was 57.58%, with the number of siblings being ≥1 (93.94%). The proportion of people who completed secondary level maternal education was 60.61%, which was higher than the proportion of people who completed secondary level paternal education (54.55%). The employment status of fathers was 96.97%. Underweight status was associated with pneumonia (AOR=5.81; 95%CI=1.07–31.68). Inadequate air humidity was associated with the incidence of pneumonia (AOR=7.37; 95%CI=1.80–30.13). Conclusion: Nutritional status and air humidity were identified as determinants of pneumonia in toddlers in Jambi city.